2017
DOI: 10.1159/000481544
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Periodontitis Is Increased in Psoriasis and Linked to Its Inverse Subtype

Abstract: Periodontitis and psoriasis are suggested to be co-occurring, chronic inflammatory conditions with overlapping characteristics. However, respective evidence is rare and data on risk factors of periodontitis in psoriasis patients are minimal. The aim of this study was to expand the evidence of psoriasis-associated periodontitis and establish a potential risk profile for periodontitis. In total, data from 209 exacerbated psoriasis patients were retrospectively analyzed on recordings of periodontitis and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Severity of psoriasis also presented a strong relationship with periodontal clinical parameters (211). A link was identify between the inverse type of psoriasis and periodontitis (212).…”
Section: Periodontitismentioning
confidence: 81%
See 1 more Smart Citation
“…Severity of psoriasis also presented a strong relationship with periodontal clinical parameters (211). A link was identify between the inverse type of psoriasis and periodontitis (212).…”
Section: Periodontitismentioning
confidence: 81%
“…A meta-analysis including two cohort studies and three casecontrol studies found that patients with periodontitis had a significantly elevated risk of psoriasis (pooled RR is 1.55, 95% CI, 1.35-1.77) (209). Vice versa, studies confirmed a significant psoriasis-associated increased risk of periodontitis (210)(211)(212), which was highest in patients with severe psoriasis and PsA (210). Severity of psoriasis also presented a strong relationship with periodontal clinical parameters (211).…”
Section: Periodontitismentioning
confidence: 98%
“…The articles excluded from the analysis, and the reasons for their exclusion, are shown in Figure 1 . The included articles were 11 case–control (Fadel et al., 2013 ; Ganzetti et al., 2015 ; Lazaridou et al., 2013 ; Mendes, Cota, Costa, Oliveira, & Costa, 2019 ; Painsi, Hirtenfelder, Lange‐Asschenfeldt, Quehenberger, & Wolf, 2017 ; Preus et al., 2010 ; Sarac, Kapicioglu, Cayli, Altas, & Yologlu, 2017 ; Sharma, Raman, & Pradeep, 2015 ; Skudutyte‐Rysstad, Slevolden, Hansen, Sandvik, & Preus, 2014 ; Woeste, Graetz, Gerdes, & Mrowietz, 2019 ) and 2 cohort studies (Keller & Lin, 2012 ; Nakib, Han, Li, Joshipura, & Qureshi, 2013 ) published in the English language between 2010 and 2019 and conducted in 13 different countries and regions across Asia, Europe, and America. Of these 13 articles, 9 showed prevalence of periodontitis or psoriasis (Antal, Braunitzer, Mattheos, Gyulai, & Nagy, 2014 ; Ganzetti et al., 2015 ; Keller & Lin, 2012 ; Lazaridou et al., 2013 ; Mendes et al, 2019 ; Nakib et al., 2013 ; Painsi et al., 2017 ; Preus et al., 2010 ; Skudutyte‐Rysstad et al., 2014 ), five reported data for continuous variables, including PD (Mendes et al., 2019 ; Sharma et al., 2015 ), clinical attachment level (CAL) (Mendes et al., 2019 ; Sharma et al., 2015 ), number of missing teeth (Skudutyte‐Rysstad et al., 2014 ; Woeste et al., 2019 ), or number of remaining teeth (Fadel et al., 2013 ; Mendes et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the definition criteria for PD, two studies (Mendes et al., 2019 ; Skudutyte‐Rysstad et al., 2014 ) used Centers for Disease Control and Prevention (CDC) and the American Academy of Periodontology (AAP) definition; three (Lazaridou et al., 2013 ; Sarac et al., 2017 ; Woeste et al., 2019 ) used the Community Periodontal Index (CPI); three (Fadel et al., 2013 ; Preus et al., 2010 ; Sharma et al., 2015 ) defined periodontitis by the evidence of radiographic alveolar bone loss; two (Antal et al., 2014 ; Ganzetti et al., 2015 ) reported CAL and/or PD; one (Keller & Lin, 2012 ) identified cases of periodontitis from the Longitudinal Health Insurance Database by diagnostic codes; one (Nakib et al., 2013 ) defined periodontitis according to self‐reported history of periodontal bone loss; and one (Painsi et al., 2017 ) did not describe the diagnosis criteria of periodontitis. The diagnosis of psoriasis in seven studies (Lazaridou et al., 2013 ; Mendes et al., 2019 ; Painsi et al., 2017 ; Sarac et al., 2017 ; Sharma et al., 2015 ; Skudutyte‐Rysstad et al., 2014 ; Woeste et al., 2019 ) was based on Psoriasis Area and Severity Index (PASI) score. In two studies, psoriasis was self‐reported (Nakib et al., 2013 ; Preus et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation